Constructing of Decent Work Index of Regency/City in Indonesia and its Influencing Factors - Nurshauma, Fiska Alfiyya; Yuniasih, Aisyah Fitri (Department of Statistics ITS, 2025)
Currently, there are still many workers in Indonesia who obtain low-quality or inappropriate jobs. This can be seen from inadequate wages, non-standard working hours, and low labour productivity. In fact, decent work is very important to reduce poverty and achieve sustainable development. Therefore, this study aims to develop a comprehensive measure of decent work, the Decent Work Index (DWI), for each regency/city in Indonesia. The DWI is compiled based on the ILO indicator framework using factor analysis method in accordance with the stages of index compilation by the OECD. In addition, this study also uses multiple linear regression to analyze the influence of education and the development of information and communication technology on decent work conditions. The results show that nine indicators are divided into three factors, namely full and productive work, rights at work, and equal opportunity and treatment in employment. Denpasar City is the city with the highest DWI, and Mamberamo Raya Regency is the regency with the lowest DWI. Meanwhile, the results of multiple linear regression shows that Mean Years of Schooling (MYS), the percentage of individuals using computers, and the percentage of individuals using e-commerce can increase the DWI.